1979
DOI: 10.1126/science.419404
|View full text |Cite
|
Sign up to set email alerts
|

Risk with Energy from Conventional and Nonconventional Sources

Abstract: Risk to human health was compared for five conventional and six nonconventional energy systems. The entire cycle for producing energy was considered, not just part. The most important conclusion drawn is that the risk to human health from nonconventional sources can be as high as, or even higher than, that of conventional sources. This result is produced only when the risk per unit energy is considered, rather than the risk per solar panel or windmill. The risk from nonconventional energy sources derives from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…The examination specifically focuses on the vulnerability of different energy systems to natural disasters, and the subsequent impact or benefit that the energy system can have in disaster situations. Because the study examines energy systems under unusual circumstances of natural disasters, it does not take into account the standard operational impacts which are the consideration of most of the standard literature on risk and the externalities of energy [41][42][43]. The alternative energy systems considered in this assessment are representative of the key modern energy sources-both conventional fossil fuels and the more recently expanding renewable energy technologies.…”
Section: Methodsmentioning
confidence: 99%
“…The examination specifically focuses on the vulnerability of different energy systems to natural disasters, and the subsequent impact or benefit that the energy system can have in disaster situations. Because the study examines energy systems under unusual circumstances of natural disasters, it does not take into account the standard operational impacts which are the consideration of most of the standard literature on risk and the externalities of energy [41][42][43]. The alternative energy systems considered in this assessment are representative of the key modern energy sources-both conventional fossil fuels and the more recently expanding renewable energy technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear energy was again the topic of a seminal paper in which Inhaber ( 15 ) compared health risks associated with a variety of conventional and nonconventional sources of electricity. Concerned that nuclear power risks were misperceived by people outside the industry, he demonstrated that nuclear and natural gas were substantially safer than oil, coal, wind, methanol, and solar (ocean thermal and hydroelectricity were intermediate).…”
Section: Historical Cases: Precision and Disputementioning
confidence: 99%
“…In addition, they showed that credible changes of some critical assumptions completely changed the comparison profile, even using Inhaber's metric of “total man‐days lost.” The Holdren et al critique was particularly telling in that Inhaber's analysis relied heavily on Holdren's earlier work. ( 15,16 ) A second critique ( 17 ) similarly reported flaws in assumptions and methods, while concluding that more careful analysis could lead to more useful conclusions.…”
Section: Historical Cases: Precision and Disputementioning
confidence: 99%
“…Here is an example from the politics of risk. In 1979, a consultant to the nuclear energy industry published a study in Science, concluding that nonconventional energy sources are more risky than nuclear and other conventional sources of energy (Inhaber, 1979). The study, which was widely publicized by the nuclear industry, was immediately attacked by scientists who held opposing views on the the risks of nuclear power (e.g., Holdren, Smith, and Morris, 1979), largely on grounds of inappropriate assumptions and calculations.…”
Section: Implications For Risk Analysismentioning
confidence: 99%